Penyampaian Pelayanan Publik (Public Service Delivery) Pada Daerah Otonom Baru - Simon S. Hutagalung (PUBLICA, 2012)
This qualitative study revealed that the problem of education and health services in the Kabupaten Pesawaran consists of three issues, namely: (1) human resources, (2) Infrastructure and, (3) budget. Problems that occur within the scope of human resources consists of the problem of quantity, distribution and motivational educators and medical personnel to provide services. Factors that affect education and health services in the region covered by the two scope, namely: (1) The condition of a dilemma in the delivery of services agency performance, (2) The relationship between the stakeholders in the education and health service delivery. In addition there are also some aspects that could be a potential raw material for the development of alternative models of public service.